PENANDA MIKROSATELIT SEBAGAI PENCIRI JATI ”PLUS” - Mariya Ulfa; Amin Retnoningsih; Endah Suwarni (PTTI, 2010)
Mariya Ulfa, Amin Retnoningsih & Endah Suwarni. 2010. Microsatellite Marker as Characterization of Teak “Plus”. Floribunda 4(1): 5–14.— The result of this study showed that all primers used were polymorphic allele. Locus Tg-AAG10 could detect polyploidy of teak accession J32 and J37 from Ngawi. The total of alleles detected was 8, with the average 6 alleles per locus. The highest amount was found in locus Tg- AAG10 (9 alleles). The genetic diversity parameter of Java teak “plus” using microsatellite marker showed high result and also could detect allele and specific genotype. Allele and specific genotype as teak fingerprint data could be detected by all three loci, so that all loci that were used in this research could be used as fingerprint of teak “plus” in Java.